Life cycle : psychological and theological perceptions - Dayringer, Richard (Routledge, 2012)
Understand the spiritual and psychological stages of human life!Life Cycle: Psychological and Theological Perceptions provides professors and students of religion, pastoral counselors, and parents with a description of human personality development from birth to death from both psychological and theological perspectives. You will examine how personalities develop and unfold as individuals grow and how they are influenced by family members and by God, helping you view the life cycle as a sacred journey. Life Cycle will help you, as a parent, to understand your children better, and as.